Inflammation in Lone Atrial Fibrillation - Yao, Shu‐Yuan (Clin Cardiol, 2009)
OBJECTIVES: This study was designed to evaluate the correlation between lone atrial fibrillation and inflammation. METHODS: A total of 411 subjects were enrolled in this study, including 333 patients with lone atrial fibrillation, and 78 controls. C‐reactive protein (CRP) and echocardiography were evaluated, and the electrocardiograph was monitored to identify cardiac rhythm at the time of blood sampling. According to the rhythm, paroxysmal atrial fibrillation was divided into presence and absence of atrial fibrillation. RESULTS: Subjects with lone atrial fibrillation had higher CRP levels than controls (media, 1.00 mg/L; IQR, 1.00–2.54 versus media, 1.00 mg/L; IQR, 1.00–1.55; p = 0.016) and subjects with persistent atrial fibrillation had higher CRP levels than those with paroxysmal atrial fibrillation (media, 1.62 mg/L; IQR, 1.00–3.98 versus media, 1.00 mg/L, IQR, 1.00–2.10; p = 0.022), and so did presence of atrial fibrillation rather than absence of atrial fibrillation (media, 2.11 mg/L; IQR, 1.00–3.60 versus media, 1.00 mg/L; IQR, 1.00–1.76; p = 0.000) in paroxysmal atrial fibrillation. However, there was no significant difference in CRP levels between persistent atrial fibrillation and presence of atrial fibrillation in paroxysmal atrial fibrillation (p = 0.992). Neither was there any difference between absence of atrial fibrillation in paroxysmal atrial fibrillation and controls (p = 0.483). In patients with lone atrial fibrillation, atrial fibrillation rhythm (B = 4.85, 95%CI: 2.61–8.99) was the only independent predictor of elevated CRP levels after adjusted covariants. CONCLUSIONS: Patients with lone atrial fibrillation had elevated CRP levels only when they were in atrial fibrillation rhythm and an elevated CRP level was not related to duration of time or history of atrial fibrillation. Copyright © 2009 Wiley Periodicals, Inc.